Nuclear Cooperation between Argentina and Brazil: Brazilian Reluctances to Limit an Expanded Strategic Partnership - Soares, Samuel Alves [UNESP]; Januario, Luiza Elena [UNESP]; Valdivieso, Cristian Daniel [UNESP] (Univ Granada, Fac Political Science & Sociology, 2020)
This paper aims to analyze how the Argentina-Brazil relations in the nuclear field were understood by the Brazilian government in three moments: in the 1980s, when the bilateral approach begins; in the 1990s when the two countries changed their approaches to the international nonproliferation regime and became part of it; and, finally, in the 2000s, when a nuclear renascence took place in Brazil. We argue that there is some hesitance concerning the level of Brazil's compromise even if its interest in nuclear cooperation with Argentina is constant. We focus on the nuclear programs, the bilateral relations, and the perceptions of international society about the nuclear projects to analyze how Brazilian authorities understood the relationship with the neighbor country in a sensitive area since the beginning of the rapprochement efforts to a moment when this process seems consolidated. The proposed thesis is that the Brazilian reluctance is explained by the configuration of a power policy expressed and taken over by different governments with a sovereign position. Brazilian reluctances have limited the possibilities for an integrative nuclear strategy between Argentina and Brazil. The article concludes that the Brazilian position has limited the possibilities of a strategic partnership in the nuclear area between Argentina and Brazil since it has chosen to limit relations with Argentina towards the axis of cooperation and not a deep integration, which It would include an opening of the country towards the exchange of sensitive knowledge pertaining to the area of international security.
Keywords: Brazil; Argentina; nuclear cooperation; Expanded Strategic Partnership